1992
DOI: 10.1007/bf01607139
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical staining patterns of tenascin in invasive breast carcinomas

Abstract: Eighty-two cases of primary invasive breast carcinoma and adjacent "normal" mammary glands were examined immunohistochemically for tenascin expression and distribution. Formalin-fixed tissues pretreated with actinase were processed by the avidin-biotin complex method using anti-human tenascin monoclonal antibody (RBC1). In normal mammary glands, tenascin was distributed around the ducts and ductules but not around the acini. In carcinomas, a high incidence of tenascin-positive cases (greater than 67%) was seen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0

Year Published

1994
1994
2003
2003

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 10 publications
3
14
0
Order By: Relevance
“…No consistent differences in tenascin localization were found among different types of carcinoma in various tissues. Tumors that exerted a desmoplastic reaction, however, showed more tenascin staining, as was also observed by Shoji et al (1992), whereas the reverse was observed in tumors with scanty stroma, such as carcinoids. In pleomorphic adenomas of the salivary gland, Soini et al (1992) observed tenascin staining in the stromal compartment, especially in dense stroma and in chondroid areas.…”
Section: Tenascinsupporting
confidence: 53%
“…No consistent differences in tenascin localization were found among different types of carcinoma in various tissues. Tumors that exerted a desmoplastic reaction, however, showed more tenascin staining, as was also observed by Shoji et al (1992), whereas the reverse was observed in tumors with scanty stroma, such as carcinoids. In pleomorphic adenomas of the salivary gland, Soini et al (1992) observed tenascin staining in the stromal compartment, especially in dense stroma and in chondroid areas.…”
Section: Tenascinsupporting
confidence: 53%
“…In advanced tumours of both DGCA and IGCA, Tn immunoreactivity in the stroma was markedly increased. These findings are in keeping with previous data on invasive tumours [16,22,26]. Metastatic islets and cell lines of DGCA and IGCA differed in their immunoreactions for Tn.…”
Section: Discussionsupporting
confidence: 92%
“…TN-C is generally found at low levels in the normal adult tissues, but is upregulated in some physiological and pathological conditions including wound healing, inÂŻammatory lesions, ÂŽbrosis and in cancer tissues (ChiquetEhrismann et al, 1995;Crossin, 1996;Mackie, 1997). Studies have demonstrated elevated TN-C expression in various human cancers, including breast (Shoji et al, 1992;Yoshida et al, 1997), lung (Kusagawa et al, 1998), colon (Sakai et al, 1993;Hanamura et al, 1997), and liver (Yamada et al, 1992). TN-C is expressed in both cancer and stromal cells, suggesting a possible role in invasive properties of the cancer cells themselves as well as in the remodeling of cancer stroma.…”
Section: Introductionmentioning
confidence: 99%